Effect of platinum impregnation on ZnO tetrapods for ethanol sensor - Hongsith N. (2014)
Platinum impregnated ZnO tetrapods were prepared and studied for the detection of ethanol vapor. ZnO tetrapods were synthesized by oxidation reaction technique by heating a mixer of zinc powder (99.99%) and hydrogen peroxide solution (30 wt.%) at 1, 000°C in air. Platinum was impregnated by dropping hydrogen hexachloroplatinate (IV) hydrate, H2Cl6Pt.aq, solution with different concentration on ZnO tetrapods and then, heated at 350°C for 1 hr. The platinum impregnated ZnO tetrapods were characterized by field emission scanning electron microscopy (FE-SEM) and energy dispersive spectroscopy (EDS) for morphology and chemical composition, respectively. The particles were observed on the surface of ZnO tetrapods. The EDS spectrum suggested that the particles were platinum. Platinum impregnated ZnO tetrapods were tested ethanol sensing properties under ethanol concentration of 50-1,000 ppm. The ethanol sensing results indicated that the sensitivity of the sensors depended on the platinum impregnated concentration. Moreover, the sensors based on platinum impregnated ZnO tetrapods of 0.035 wt.% exhibited higher sensitivity compare to those of non-impregnation ZnO tetrapods. © 2008 Trans Tech Publications, Switzerland.